"Don't call me a Cajun!": race and representation in Louisiana's Acadiana region. Issue 1 (2nd January 2019) - Giancarlo, Alexandra
ABSTRACT: In southwestern Louisiana, the public sphere is dominated by the image of the Cajuns, presented as a hardy, likable people who have overcome significant obstacles since their arrival as Acadians in the late eighteenth century. Across the cultural region designated "Acadiana, " which comprises 22 counties, nearly 30% of the population is black (or Creole, mixed-race peoples generally identifying as black). Contributions of non-whites to the region's history are usually not incorporated into the public historical narrative, and the erasure of these groups' influences on the state's cultural "gumbo" has profound symbolic and material consequences. Black/Creole residents note that much of their culture – primarily music and foodways – has been repackaged as Cajun or subsumed under the Cajun label and that they are unable to take advantage of the benefits that Creole-oriented tourism could bring to a region in which half of the counties are designated "black high poverty parishes." Using mixed methods, including interviews, archival analysis, and census data, this paper explores the social, political, and economic consequences of the domination of Cajuns in the south Louisiana memorial and representational landscape and argues that commemorative silences in what Alderman et al . have called the "memorial arena" perpetuate a hegemonic social order.